Nationality Acquisition for children from mother side in Omani law compared study with Malaysian law - Alnofli, Hassan Obaid Zayid (Journal of Economic, Administrative and Legal Sciences, 2022)
This research addressed the issue of acquiring nationality by boys through the mother in Omani law compared to Malaysian law, and this is what the research presented in its four chapters, explained the concept of nationality and the stages of its development by positive laws and dealt with the concept of nationality in Omani law and Malaysian law and the stages of its development in general, and dealt with the second chapter methods and conditions of acquisition of citizenship in accordance with international laws and status and dealt with the chapter how to acquire citizenship on the international scale in accordance with treaties and International conventions and laws and how to acquire Omani nationality and Malaysian citizenship in terms of the conditions of each country, chapter 3 spoke about the effects of acquiring citizenship and explained this chapter the difference between the legal effects of acquiring citizenship for the children of Omani mother married non-Omani in Omani law and the legal effects of acquiring citizenship for the children of Malaysian mothers married to non-Malaysians, chapter 4 touched on the opinions of international specialists in general and in Oman in granting citizenship to Omani children Married non-Omanis, and the opinions of specialists in Oman were divided into two directions, the first is a trend in favor of granting citizenship to the children of omani mothers married to a foreigner, and the other trend against the granting of Omani citizenship to the children of Omani mothers married to a foreigner, and the research has reached several results, the most important of which is that the nationality is acquired by the child either by his father or mother, as indicated by most legislation on countries, in particular the state of Oman and malaysia. They are the subject of this research.